Potential of spent fluid cracking catalyst (FCC) waste for low-carbon cement production - Pavia, Sara (My University, 2023)
Spent fluid cracking catalyst (FCC) waste is produced to convert petroleum crude oil into gasoline, and its main component is a reactive zeolite known as faujasite. This paper studies low-energy treatments to enhance reac- tivity. When untreated, the spent FCC has outstanding activity, and a fast set which delivered significant strength (6–10 MPa) and a high mechanical index (MI=14). Calcination (up to 800 ◦ C) is not enough to amorphize the faujasite and increase reactivity. However, NaOH-fusion is highly efficient. Even at low temperature (450 ◦C), NaOH-fusion breaks down the zeolite structure, dissolving Si4+ that forms cementing hydrates with high Ca/Si and Si/Al ratios which delivered high strengths. NaOH-fusion at 450 ◦C totally amorphized the zeolite resulting in high strength (9–13 MPa) and outstanding MI>22; superior to pozzolans, and closer to cementitious materials. Fusion at 600 ◦C reorganises some of the amorphous phase into a silicate whose hydrates provided the greatest strengths (over 16 MPa) and an outstanding MI of 24. Na2CO3-fusion at 600 ◦C did not alter the spent FCC but provided CO3 2 which formed calcite cements. These initially densified the matrix providing strength but lowered long-term strength and workability. Acid-etching partially dissolved spent FCC particles which improved early activity but caused a loss of soluble Si4+ and Al3+ that reduced the ultimate strength. Due to the low organic matter in the spent FCC, oxidation did not increase reactivity. The spent FCC is highly pozzolanic, it can safely reduce the embodied carbon of cements: concentrations of heavy metals are either traces or insignificant. Therefore, they can easily immobilise in a stable matrix.
PUBLISHED
Keywords: Alkali fusion; Calcination; Mechanical index; Chapelle test; Pozzolanic activity; Low-carbon cement; Reactivity; Fluid cracking catalyst (FCC); Spent FCC waste; Nanoscience & Materials; Smart & Sustainable Planet